Effect of high magnetic field annealing on microstructure, texture, and properties of high-strength non-oriented silicon steels - Qiuyue Wen; Zhaoyang Cheng; Sizhou Liu; Xinyang Tan; Yunxiang Chen; Jing Liu (Journal of Materials Research and Technology)
The challenge in high-strength non-oriented silicon steel is the synergistic enhancement of both strength and magnetic properties, which are both significantly influenced by microstructure and texture of the steel. To address this, a novel high magnetic field annealing was employed to modify the microstructure and texture of the steel, aiming for a concurrently optimization of these properties. The results indicated that both the iron loss and strength decreased with increasing annealing temperature, whereas the magnetic induction intensity increased firstly and then decreased. The application of a high magnetic field meaningfully enhanced the magnetic properties of non-oriented silicon steel, whereas the strength of the steel was significantly decrease at 750 °C, but this decrease was reduced at higher temperature. The application of magnetic field reduced the Gibbs free energy of the system during the recrystallization process resulting in a facilitation of recrystallization. During low-temperature annealing (750–800 °C) in the high magnetic field, the dislocation density decreased, and internal stress was reduced, leading to a significant reduction in hysteresis loss and an improvement in magnetic properties. However, the reduction in dislocation density resulted in a substantial deterioration of strength at low temperature. With increasing annealing temperature, the enhanced grain growth with the application of magnetic field lead to an increase in magnetic induction intensity, whereas the grain boundary strengthening contribution decreased, resulting in a decrease in strength. Furthermore, the optimal comprehensive properties were achieved by annealing at 850 °C with a high magnetic field, which yielded a magnetic induction intensity B5000 of 1.679 T, a high-frequency iron loss P1.0/400 of 21.44 W/Kg, and a yield strength of 508 MPa, are well-suited for utilization in the drive motors of new energy vehicles.